Oil from Chinese deposits - Kurt Wiesegart (Intereconomics, 1980)
From 18–25 March the United Nations' “International Meeting on Petroleum Geology” will take place in China, a country whose oil reserves up to the mid-sixties had been judged by foreign observers to be minute and the development of her oil sector of no major importance. Today, with an annual crude output of 106 mn tons, China already ranks ninth among the world's oil producers. And, with the prospect of a further advance towards leadership among producers and exporters of the coveted energy material, the West is showing growing interest in China's energy potential. How real is this prospect?
Keywords: 330